Does Income Diversification Improve Bank Performance? A Panel Study of Regional Development Banks and Commercial Banks in Indonesia - Rizka Rimasda; Maria Ulpah (UNIVED Press, 2026)
This study examines the effect of income diversification on bank performance in Indonesia using a Fixed Effect model with clustered standard errors. Bank performance is measured by ROA, ROE, SHROA, SHROE, and Z_SCORE, while income diversification is proxied by DIV_ADJ. The model also includes bank type, digitalization, and several control variables such as bank size, capital adequacy, operational costs, credit risk, and macroeconomic conditions. The results show that income diversification has a positive and significant effect only on risk-adjusted performance (SHROA and SHROE), but not on conventional profitability or stability. The moderating effects of bank type and digitalization are partial and inconsistent. Among control variables, bank size is the most consistent determinant of performance, while capital adequacy improves stability and credit risk reduces performance. Overall, income diversification mainly enhances bank performance through risk-adjusted measures, and its effectiveness depends on bank characteristics and risk management quality.